STAD: STRATEGI MENINGKATKAN NILAI UJIAN NASIONAL BAHASA INDONESIA PESERTA DIDIK KELAS XII AK 2 SMKN 1 BANYUMAS SEMESTER GENAP 2014/2015 - Andit Dwi Susanto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
The purpose of this study are: (1) The teacher can apply STAD cooperative learning strategies to improve the quality of learning Indonesian. (2) Through a cooperative learning model STAD, able to increase the value of National Examination in subjects Indonesian. To measure the achievement of these objectives is done by setting the achievement indicators of learning that is at least 80% of students scored above the value of completeness. (3) School strives to develop innovative learning programs, improving the quality of school more conducive and filled with the power of innovation and creativity. Class Action Research was conducted in two cycles, with research subjects learners class XII AK 2 SMK Negeri 1 Banyumas totaling 31 students consisting of one male and 30 female. From the data analysis can be concluded: (1) The teacher can apply the strategy of